In Memoriam: Douglas Walton 1942-2020 - Tindale, Christopher (Informal Logic, 2020)
We deeply mourn the sudden and completely unexpected death of our friend and colleague on 3 January 2020, a gentle and unassuming giant in the fields of informal logic and argument theory.